Pengaruh Sistem Akuntansi Manajemen, Desentralisasi Terhadap Kinerja Manajerial Dengan Ketidakpastian Lingkungan Sebagai Variabel Moderasi - Nanda Febiana; Elvin Bastian; Fara Fitriyani (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to examine the effect of management accounting systems and decentralization on managerial performance with environmental uncertainty as a moderating variable. This research is a type of quantitative research, data collected using primary data and questionnaires to obtain information to respondents, namely middle managers who work in the hotel industry in Serang Regency, the method used in this research is purposive sampling using SPSS. The results of this study are 1) Management accounting system has a significant effect on managerial performance, 2) Decentralization has a significant effect on managerial performance 3) Management accounting system has a significant effect on managerial performance which is moderated by environmental uncertainty variables, 4) Decentralization has a significant effect on moderated managerial performance. by environmental uncertainty.